Vacina antivariólica: visões da Academia de Medicina no Brasil Imperial Smallpox vaccine: views of the Academy of Medicine in Imperial Brazil - Tania Maria Fernandes (História, Ciências, Saúde: Manguinhos, 2004)
A Academia de Medicina ocupou, no Brasil Império, importante espaço na promoção de debates e discussões acerca da medicina no país, simbolizando o movimento de tentativa de organização e busca de legitimação do corpo médico brasileiro daquele momento. Este artigo trata da atuação da Academia, no que diz respeito à vacina antivariólica e suas concepções e práticas, desde a criação como Sociedade de Medicina do Rio de Janeiro até sua transformação em Academia Nacional de Medicina, no final do século XIX. Os periódicos da instituição, fonte central deste estudo, retratavam o pensamento e a prática médica brasileiras e ressaltavam a carência de pesquisas e a necessidade de maior leitura para elaboração de estudos próprios. Divulgavam trabalhos elaborados e já publicados em outros países, ou discussões apontadas por médicos brasileiros, inicialmente voltados para casos e estatísticas clínicas e hospitalares e, posteriormente, incorporando experimentos laboratoriais à clínica. In Imperial Brazil, the Academy of Medicine played an important role in promoting debates and discussions about local medicine. It was a symbol of the movement to try to organize the Brazilian medical body and lend it legitimacy. The article focuses on issues surrounding the Academy's activities regarding the smallpox vaccine and its conceptions and practice, covering the period from the Academy's birth as the Rio de Janeiro Society of Medicine till its transformation into the National Academy of Medicine, when Brazil became a Republic at the close of the nineteenth century. The main source for this study were the Academy's periodicals, which portrayed Brazilian medical thought and practice throughout the nineteenth century and underscored the lack of research and the need for greater reading on the topic so local studies could be conducted. These publications were devoted to disseminating works that had already been published in other countries or to discussions raised by Brazilian physicians. The latter at first targeted clinical and hospital cases and statistics and then later, starting in the 1880s, began to incorporate laboratory experiments.